Control of a Clonal Outbreak of Multidrug-Resistant Acinetobacter baumannii in a Hospital of the Basque Country after the Introduction of Environmental Cleaning Led by the Systematic Sampling from Environmental Objects - Delgado Naranjo, Jesús; Villate Navarro, José Ignacio; Sota Busselo, Mercedes; Martínez Ruíz, Alberto; Hernández Hernández, José María; Torres Garmendia, María Pilar; Urcelay López, María Isabel (Interdisciplinary Perspectives on Infectious Diseases, 2013)
Background. Between July 2009 and September 2010, an outbreak of multidrug-resistant (MDR) Acinetobacter baumannii was detected in one critical care unit of a tertiary hospital in the Basque Country, involving 49 infected and 16 colonized patients. The aim was to evaluate the impact of environmental cleaning and systematic sampling from environmental objects on the risk of infection by MDR A. baumannii. Methods. After systematic sampling from environmental objects and molecular typing of all new MDR A. baumannii strains from patients and environmental isolates, we analyzed the correlation (Pearson’s r) between new infected cases and positive environmental samples. The risk ratio (RR) of infection was estimated with Poisson regression. Results. The risk increased significantly with the number of positive samples in common areas (RR = 1.40; 95%CI = 0.99–1.94) and positive samples in boxes (RR = 1.19; 95%CI = 1.01–1.40). The number of cases also positively correlated with positive samples in boxes (r=0.50; P<0.05) and common areas (r=0.29; P=0.18). Conclusion. Once conventional measures have failed, environmental cleaning, guided by systematic sampling from environmental objects, provided the objective risk reduction of new cases and enabled the full control of the outbreak.